2021
DOI: 10.1039/d0ra08903f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ni/Co mass ratio and NiO–Co3O4 loading on catalytic performance of NiO–Co3O4/Nb2O5–TiO2 for direct synthesis of 2-propylheptanol from n-valeraldehyde

Abstract: NiO–Co3O4/Nb2O5–TiO2 catalyst with a Ni/Co mass ratio of 8/3 and NiO–Co3O4 loading of 14% shows the best catalytic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Similar to natural enzymes, diverse experimental conditions can affect the peroxidase-like properties of NiCo 2 S 4 (PVP) NPs and NiCo 2 S 4 (CTAB) NPs, such as the reaction temperature and pH. , We choose NiCo 2 S 4 (PVP) NPs, which had higher catalytic activity, for the optimization experiment. Figure S7a shows the improvement of the solution in absorbance along with the enhancement concentration of NiCo 2 S 4 (PVP) NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to natural enzymes, diverse experimental conditions can affect the peroxidase-like properties of NiCo 2 S 4 (PVP) NPs and NiCo 2 S 4 (CTAB) NPs, such as the reaction temperature and pH. , We choose NiCo 2 S 4 (PVP) NPs, which had higher catalytic activity, for the optimization experiment. Figure S7a shows the improvement of the solution in absorbance along with the enhancement concentration of NiCo 2 S 4 (PVP) NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Transition metal chemicals (TMCs) have been widely used in research as catalysts targeting HER/OER due to their abundant resource storage, low cost, and environmental friendliness, especially nickel-based materials. However, it was found that their low intrinsic conductivity is a huge obstacle to overcome to replace the precious metal HER/OER catalysts, . Nowadays, the main methods for the preparation of Ni-based catalysts are the hydrothermal method, the sol–gel method, the vapor-phase deposition method, the chemical method, and the electrodeposition method. , The hydrothermal method requires more stringent preparation conditions. The sol–gel method is expensive and has a lengthy preparation cycle.…”
Section: Introductionmentioning
confidence: 99%
“…17−23 However, it was found that their low intrinsic conductivity is a huge obstacle to overcome to replace the precious metal HER/OER catalysts, 24 . 25 Nowadays, the main methods for the preparation of Ni-based catalysts are the hydrothermal method, 26 the sol− gel method, 27 the vapor-phase deposition method, 28 the chemical method, 29 and the electrodeposition method. 30,31 The hydrothermal method requires more stringent preparation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9–11 ] As an important aldehyde, n ‐valeraldehyde is a significant intermediate in organic synthesis and raw materials of spices, which is widely applied in organic synthesis fields. [ 12–17 ] However, the excessive use of n ‐valeraldehyde puts the environment and humans in danger. [ 10,18,19 ] Therefore, the development of a green and eco‐friendly approach to reduce n ‐valeraldehyde pollution is of great significance.…”
Section: Introductionmentioning
confidence: 99%